The outcome of ART in males with impaired spermatogenesis - V S Mangoli (Journal of Human Reproductive Sciences, 2008)
Aims: This study was conducted to evaluate the outcomes of assisted reproductive technology (ART) procedures, viz., intrauterine insemination (IUI), in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) in males with impaired spermatogenesis. Settings and Design: The subjects of the study were infertile couples who were undergoing ART treatment due to male factor indications. The project was designed to correlate the outcome of the ART treatment and its efficacy in different study groups. Methods: Males were grouped as: 1. oligozoospermia (n = 153), 2. asthenoteratozoospermia (n = 158), 3. obstructive azoospermia (n = 110) and 4. nonobstructive azoospermia (n = 58). Patients from groups 1 and 2 were considered for IUI, IVF and ICSI. Those from group 3 were considered for IVF and ICSI and the 4th group underwent only ICSI treatment. Results: Oligozoospermia showed lower pregnancy rates with IUI than with both IVF and ICSI. An average minimum native and postharvest count was obtained to get an acceptable IUI outcome. Asthenoteratozoospermia had the lowest pregnancy rate with IUI as compared to IVF, whereas ICSI showed significantly higher pregnancy rates in this group. Obstructive azoospermia showed significant improvement with ICSI over IVF. In nonobstructive azoospermia, ICSI resulted in a 27.58% pregnancy rate. Conclusion: The IUI outcome was impressive though less effective whereas there was no difference between the IVF and ICSI outcomes in oligozoospermia. In asthenoteratozoospermia, ICSI showed a significant advantage over IUI and IVF, with IUI resulting in poor outcome in this group. In obstructive azoospermia, ICSI had a distinct advantage over IVF whereas in nonobstructive azoospermia, ICSI, the only option, was found to be effective and helpful in achieving an acceptable pregnancy rate.